The effect of cobalt-chloride on the production parameters and homogenity of barramundi (Lates calcarifer) larvae - Fehér, Milán; Baranyai, Edina; Bársony, Péter; Simon, Edina; Posta, József; Stündl, László (Acta Agraria Debreceniensis, 2013)
Barramundi (Lates calcarifer) is a predatory fish species native in Southeast Asia and Australia. Based on the geothermal potentiality of Hungary the high market potential warm-water fish barramundi can be produced economically. Living nourishment organisms such as Artemia nauplii play an essential role in the larval rearing of barrramundi. However, zooplanktons in natural aquatic enviroments contain minerals in a higher concentration than the usually fed newly hatched Artemia. Therefore the goal of recent study was to investigate the effect of cobaltchloride on the larval growth and survival of barramundi when fed individually and combined with Zn and Mn supplemented Artemia.In our experiment a 24 hours period was used for the enrichment of newly hatched Artemia nauplii with cobalt chloride in itself, as well as in combination with zinc sulphate and manganese chloride. A total of 1900 barramundi larvae from 15–30 day post hatching were fed with supplemented Artemia in 9 groups of treatments in duplicate. The growth performance and elemental concentration of 40 larvae from each group was determined. All the groups produced significantly improved growth compared to the control (p